Leveraging IPFS to Build Secure and Decentralized Websites in the Web 3.0 Era - Maulana, Imam Ryan; Rahardja, Untung; Azizah, Nur; Rakhmansyah, Mohamad; Komara, Maulana Arif (Pandawan Sejahtera Indonesia, 2025)
In recent years, Web 3.0 has gained significant attention due to its potential to create a more secure and decentralized internet. The background of this research lies in the growing demand for data privacy and security, which traditional Web 2.0 platforms fail to provide.The objective of this study is to explore how IPFS (InterPlanetary File System) can be leveraged to build decentralized websites that prioritize security and user privacy in the Web 3.0 ecosystem. The method involves a qualitative approach, including a case study where IPFS is utilized to develop a decentralized website, followed by a series of performance and security tests. The performance tests revealed that IPFS-based websites achieved a 99.2% uptime compared to 96.5% in traditional websites, and reduced server failure rates by approximately 35%. These quantitative results confirm that IPFS provides higher resilience against data breaches and server failures while reducing reliance on single points of failure. The conclusion drawn from this research indicates that IPFS is a promising technology for developing secure, decentralized websites in the Web 3.0 era, offering an enhanced user experience with improved privacy, data security, and scalability. The findings suggest that adopting IPFS for web development could pave the way for the next generation of decentralized applications, contributing to the ongoing transformation of the internet.